The Deep Biosphere in Terrestrial Sediments in the Chesapeake Bay Area, Virginia, USA - Breuker, Anja; Koeweker, Gerrit; Blazejak, Anna; Schippers, Axel (Frontiers in Microbiology, 2011)
For the first time quantitative data on the abundance of Bacteria, Archaea and Eukarya in deep terrestrial sediments are provided using multiple methods (total cell counting, quantitative real-time PCR (Q-PCR) and catalyzed reporter deposition – fluorescence in situ hybridization (CARD-FISH)). The oligotrophic (organic carbon content of ~ 0.2 %) deep terrestrial sediments in the Chesapeake Bay area at Eyreville, Virginia, USA, were drilled and sampled up to a depth of 140 m in 2006. The possibility of contamination during drilling was checked using fluorescent microspheres. Total cell counts decreased from 109 to 106 cells per g dry weight (dw) within the uppermost 20 m depth, and did not further decrease with depth below. A significant proportion of the total cell counts could be detected with CARD-FISH within the uppermost 7 m depth. The CARD-FISH numbers for Bacteria were about an order of magnitude higher than those for Archaea. The dominance of Bacteria over Archaea was confirmed by Q-PCR. The down core quantitative distribution of prokaryotic and eukaryotic small subunit ribosomal RNA genes as well as functional genes involved in different biogeochemical processes was revealed by Q-PCR for the uppermost 10 m and for 80-140 m depth. Eukarya and the Fe(III)- and Mn(IV)-reducing bacterial group Geobacteriaceae were almost only found in the uppermost meter (arable soil), where reactive iron was detected in higher amounts. The bacterial candidate division JS-1 and the classes Anaerolineae and Caldilineae of the phylum Chloroflexi, highly abundant in marine sediments, were found up to the maximum sampling depth in high copy numbers at this terrestrial site as well. A similar high abundance of the functional gene cbbL encoding for the large subunit of RubisCO suggests that autotrophic microorganisms could be relevant in addition to heterotrophs. The functional gene aprA of sulfate reducing bacteria was found within distinct layers up to ca. 100 m depth in low copy nu